Late in the day a novel - Hadley, Tessa 1956- (Harper, 2019)
"Alexandr and Christine and Zachary and Lydia have been friends since they first met in their twenties. Thirty years later, Alex and Christine are spending a leisurely summer's evening at home when they receive a call from a distraught Lydia: she is at the hospital. Zach is dead. In the wake of this profound loss, the three friends find themselves unmoored; all agree that Zach, with his generous, grounded spirit, was the irreplaceable one they couldn't afford to lose. Inconsolable, Lydia moves in with Alex and Christine. But instead of loss bringing them closer, the three of them find over the following months that it warps their relationships, as old entanglements and grievances rise from the past, and love and sorrow give way to anger and bitterness"...
Keywords: FICTION / Literary / bisacsh; FICTION / Psychological / bisacsh; FICTION / Family Life / bisacsh; FICTION / Literary; FICTION / Psychological; FICTION / Family Life